2019
DOI: 10.1186/s12884-019-2363-y
|View full text |Cite
|
Sign up to set email alerts
|

Caregiving can be costly: A qualitative study of barriers and facilitators to conducting kangaroo mother care in a US tertiary hospital neonatal intensive care unit

Abstract: Background Preterm birth is a leading cause of morbidity and mortality in children under five and often requires a newborn to have an extended stay in a neonatal intensive care unit (NICU). Maternal engagement, such as visiting the NICU to provide kangaroo mother care (KMC), can improve outcomes for preterm infants but requires significant investment of time and resources. This study sought to understand barriers and facilitators to provision of KMC in the NICU. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
66
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 51 publications
(59 reference statements)
4
66
0
4
Order By: Relevance
“…Currently, KMC is considered one of the most cost-effective interventions to promote the wellbeing of preterm infants, and has been widely adopted in many countries, such as in Africa, Asia, America, Europe, and Latin American and the Caribbean [6][7][8]. It was estimated that KMC was practiced in some form (mostly intermittent) in 82% of all neonatal intensive care units (NICUs) in the United States [9].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, KMC is considered one of the most cost-effective interventions to promote the wellbeing of preterm infants, and has been widely adopted in many countries, such as in Africa, Asia, America, Europe, and Latin American and the Caribbean [6][7][8]. It was estimated that KMC was practiced in some form (mostly intermittent) in 82% of all neonatal intensive care units (NICUs) in the United States [9].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, KMC is considered one of the most cost-effective interventions to promote the well-being of preterm infants, and has been widely used including in high-income countries. It was estimated that KMC was practiced in some form (mostly intermittent) in 82% of all neonatal intensive care units (NICUs) in the United States [8].…”
Section: Introductionmentioning
confidence: 99%
“…The present findings reveal that both family SES and family language should be individual targets for programmatic interventions to reduce disparities in KC. Recent studies have shown that both disadvantaged individual (e.g., psychological and physical wellness) and systemic (e.g., parental leave policies) factors impede the frequency and duration of KC provided by parents in the NICU 25,26 . Barriers to KC may also overlap with those known to impede parental visitation, such as unemployment or low income, lack of support for other children (e.g., childcare), health insurance, marital status, parents' age, transportation, and work or household responsibilities 39,40 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the many apparent benefits of KC, however, several barriers may reduce opportunities for such practice, including parental factors (e.g., rates of visitation, family comfort with the practice) and health system factors (e.g., unit design, adequate staff support, parent educational programs, access to translators) 3,[20][21][22][23][24][25][26][27][28] . Parents and health care providers are also susceptible to cultural norms and personal beliefs that affect the frequency and amount of KC 20,21,25 .…”
Section: Introductionmentioning
confidence: 99%